Analisis Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV Hilal Dermawan Anugrah - Hilmi, Ripan; Herdian, Faldy (Jurnal Online Manajemen ELPEI, 2024)
The success and survival of a company is greatly influenced by the performance of its employees. This is because optimal performance from every individual in the organization plays an important role in achieving company goals and maintaining smooth operations. Employees who perform well not only make a positive contribution to achieving business targets, but also form the foundation for the company's sustainable growth and competitiveness in the market. The aim of this research is to carry out an analysis of work motivation and discipline at CV Hilal Dermawan Anugrah, to carry out an analysis of performance at CV Hilal Dermawan Anugrah, and how to analyze the influence of work motivation and discipline on the performance of CV Hilal Dermawan Anugrah employees. Mangkunegara (2018; 93) states that motivation is a condition that moves employees to be able to achieve the goals of their motives.  Motivation is a condition or energy that moves employees who are directed or aimed at achieving the company's organizational goals. A pro and positive mental attitude towards work situations is what strengthens work motivation to achieve maximum performance. Keith Davis in Mangkunegara, (2018; 129) states that work discipline is a management implementation to strengthen organizational guidelines. According to Rivai and Basri (2015; 14) in Nasution and Setiawan (2021) say that the definition of performance is the willingness of a person or group of people to carry out an activity and perfect it in accordance with responsibilities with the results as expected. This research was carried out using a descriptive qualitative approach at the CV Hilal Darmawan Nugraha Company with calculations using averages. The results of this research show that the average for the motivation variable is 34% if we compare it with the criteria then the value is in the Poor/Low category then the average for the Discipline variable is 36% if we compare it with the criteria then the value is at Poor category, employee performance related to achieving production targets is not good, the company is still faced with challenges related to product quality. Efforts are continuously made by the head of production and company owners to ensure that every product produced meets high quality standards and employee motivation has a significant impact on their performance. High levels of motivation tend to be positively related to achieving work goals and better productivity and work discipline has a direct impact on employee performance. Disciplined employees tend to maintain order and efficiency in the work process, which ultimately contributes to achieving the Company's goals